The relevance of bird-in-hand theory to Shariah-inclined investors: a case study of Malaysia / Fareiny Morni , Azreil Mirzza Iskandar and Azilawati Banchit - Morni, Fareiny; Iskandar, Azreil Mirzza; Banchit, Azilawati (Universiti Teknologi Mara, Selangor: Puncak Alam Campus: Faculty of Business and Management, 2019)
The purpose of this study is to identify whether the wealth of Shariah-inclined investors is affected by dividend policy. This study is different from other studies because earlier studies do not differentiate between Shariah-compliant and non-Shariah compliant stocks, creating a gap for dividend signaling theory and bird-in-hand theory on Shariah-compliant financial products. This study employs panel data analysis and multiple linear regression with the most recent data representing eight (8) out of twelve (12) sectors in the Malaysian stock market. Dividend per share and retained earnings per share are used as a proxy for dividend policy while market price per share is used as a proxy for shareholders’ wealth. It was found that for Shariah-compliant stocks, both dividend per share and retained earnings per share are insignificant in affecting shareholders’ wealth. Unlike other studies on dividend policy which do not discriminate between Shariah-compliant and non-Shariah compliant stocks, this study finds that dividend policy to be irrelevant to Shariah-inclined investors.